1999
DOI: 10.1111/j.1600-065x.1999.tb01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation by viruses: the myxoma virus story

Abstract: Myxoma virus is a poxvirus pathogen of rabbits that has evolved to replicate successfully in the presence of an active immune response by an infected host. To accomplish this, the virus has developed a variety of strategies to avoid detection by or obstruct specific aspects of the antiviral response whose consolidated action is antagonistic to virus survival. We describe two distinct viral strategies carried out by viral proteins with which myxoma virus subverts the host immune response. The first strategy is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(103 citation statements)
references
References 112 publications
(83 reference statements)
0
100
0
3
Order By: Relevance
“…One particular mechanism conceived by MV to subvert the host immune response is carried out by two related sets of immunomodulatory proteins described as virokines and viroreceptors [74,87]. These virus-encoded proteins target specific pathways of the host immune system used to coordinate antiviral and early inflammatory responses directed against viral infection [64,74].…”
Section: Virokines and Viroreceptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…One particular mechanism conceived by MV to subvert the host immune response is carried out by two related sets of immunomodulatory proteins described as virokines and viroreceptors [74,87]. These virus-encoded proteins target specific pathways of the host immune system used to coordinate antiviral and early inflammatory responses directed against viral infection [64,74].…”
Section: Virokines and Viroreceptorsmentioning
confidence: 99%
“…This leads to a series of downstream events ultimately resulting in the digestion of key structural proteins in the cytoplasm and degradation of chromosomal DNA. Viruses with larger genomes, such as poxviruses, have evolved immunomodulatory proteins which function to inhibit host-cell apoptotic responses during early stages of viral infection [74,94]. These anti-apoptotic effectors have been shown to manipulate the cell death pathways within the cell in a variety of ways, including the inhibition of caspases and disruption of key mitochondrial checkpoints to prevent apoptosis [22,23,94].…”
Section: Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…108,109 Furthermore, it has also been demonstrated that viral manufactured soluble binding proteins specific to TNF and other viral toxic cytokines such as interferon are also produced by other viruses including poxviruses, cytomegalovirus, herpesviruses, and adenoviruses. 91,[110][111][112][113][114][115] Late viral genes encode structural proteins for the capsid and viral internal core. 89 A great deal of preclinical work has been carried out utilizing modified capsid components to improve cancer targeting and reduce nontarget cell uptake.…”
Section: Onyx 015mentioning
confidence: 99%
“…67,68 Interestingly, several wild-type viruses actually produce soluble binding proteins specific to TNF. [69][70][71][72][73][74][75] Viral-produced TNF binding proteins have a similar extracellular domain as the human TNF receptor, but lack both the membrane anchor and cytoplasmic domains. [76][77][78] Given the evidence that TNF induction may affect adenoviral survival, particularly with ONYX-015 which does not contain the E3 region expressive of 14.7 protein, we have initiated a pilot trial testing the combination of ONYX-015 with Enbrel (soluble TNF receptor) in cancer patients.…”
Section: Pilot Trial Of Intravenous Infusion Of a Replication-selectimentioning
confidence: 99%